Cost‐utility analysis of add‐on Qili Qiangxin capsules in chronic heart failure with reduced ejection fraction in China - Lu Wang; Yinglin Wang; Quan Zhao (ESC Heart Failure, 2025)
Abstract Aims The study aimed to analyse the cost‐utility of Chinese patent medicine Qili Qiangxin (QLQX) capsules in heart failure with a reduced ejection fraction from the healthcare payer's perspective. Methods and results From the perspective of the healthcare payer, a Markov model was established to estimate the cost‐utility of adding QLQX capsules to standard treatment versus standard treatment. A 19‐year lifetime horizon was chosen with a 3‐month cycle in the base case analysis. The discount rate of cost and utility is 5%. Total costs and quality‐adjusted life years (QALYs) for QLQX and standard treatment were simulated over a 19‐year lifetime horizon by the Markov model using TreeAge Pro 2022. The incremental cost‐utility ratio (ICUR) was compared with the willingness‐to‐pay thresholds (the GDP per capita). The one‐way sensitivity analysis and probability sensitivity analysis were conducted. Over a 19‐year lifetime horizon, the mean total costs in the QLQX group and standard treatment group were 56 151.75 CNY and 30 099.69 CNY, respectively. The QALYs in the QLQX group were also greater than those in the standard treatment group (4.63 QALYs vs. 4.17 QALYs). The ICUR was 57 381.85 CNY per QALY, which was lower than the willingness‐to‐pay threshold (89 358 CNY). The one‐way and probability sensitivity analyses showed that the results were robust. The inputs with the largest impact on ICUR were the cardiovascular mortality in both groups. At a willingness‐to‐pay threshold of 89 358 CNY, adding QLQX capsules to standard treatment was preferred over standard treatment alone in 51.10% of the 1000 PSA samples. Conclusions This cost‐utility analysis suggested that adding QLQX capsules seems to be cost‐effective of heart failure with a reduced ejection fraction patients from the healthcare payer's perspective in China. Future studies of QLQX capsules based on different economic systems and medical environments were also needed.